2020
DOI: 10.1002/adfm.201910536
|View full text |Cite
|
Sign up to set email alerts
|

Robust Organoalkoxysilanes as Red Unconventional Fluorescent Platform

Abstract: Unconventional fluorescent materials have attracted intense and continuous attention due to the facile processability, excellent biocompatibility, and high availability. However, for the lack of suitable unconventional fluorescent platform, unconventional luminophore‐based fluorescent probes have not been applied in the biological field, especially in the detection of bioactive molecules. In this work, unconventional red fluorescence is observed from a series of organoalkoxysilanes for the first time. Particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Apart from conventional fluorescent molecules composing of aryl groups, in recent years, unconventional luminescent siloxane molecules that do not contain any of the conjugated systems have also received much attention and become an important branch in this field. In unconventional fluorescent molecules, electron-rich atoms such as sulfur and nitrogen are present and interact with silicon atom [ 38 , 39 ]. In addition, the flexible Si-O bond is conducive to fluorescent emission [ 40 ].…”
Section: Classification Of Organosilicon Fluorescent Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from conventional fluorescent molecules composing of aryl groups, in recent years, unconventional luminescent siloxane molecules that do not contain any of the conjugated systems have also received much attention and become an important branch in this field. In unconventional fluorescent molecules, electron-rich atoms such as sulfur and nitrogen are present and interact with silicon atom [ 38 , 39 ]. In addition, the flexible Si-O bond is conducive to fluorescent emission [ 40 ].…”
Section: Classification Of Organosilicon Fluorescent Materialsmentioning
confidence: 99%
“…Most unconventional luminescent siloxane molecules have a low emission wavelength, which is mainly located in UV, blue and green regions. Zuo et al [ 38 ] found Si–O bridged organoalkoxysilanes were capable of emitting unexpected red fluorescence (SiORed-1–6). Inspired by the desired red emission, SiO-Red-7 was further constructed and applied to detect NO in lysosomes and in vivo accompanied by a blue fluorescence quenching and a red fluorescence enhancement ( Figure 5 b).…”
Section: Classification Of Organosilicon Fluorescent Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, the resulting AMI products exhibit very strong fluorescence in both the solution state and aggregate state. Because the AMI possesses only a small heterocyclic ring without any typical aromatic moiety, such unusual high luminescence can be regarded as nontraditional intrinsic luminescence (NTIL). In this aspect, some heteroatom-rich natural products and synthetic polymers without conjugated aromatic structures have been reported to show NTIL. Despite such intriguing properties of the resulting products obtained by this unique multicomponent tandem reaction, few efforts have been devoted to facilitate it into a powerful tool for the synthesis of heterocyclic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6,7 ] In comparison with conventional fluorescent polymers, the unconventional fluorescence polymers without traditional chromophores have attracted a great deal of interest because of their facile preparation, excellent water solubility and good biocompatibility. [ 8–22 ] Among of unconventional fluorescent compounds, tertiary amine chromophore polymers with intrinsic fluorescence and stimulus responsiveness, which have proved to be an effective biomedical application materials and been extensively studied. [ 23–28 ]…”
Section: Introductionmentioning
confidence: 99%